2009
DOI: 10.1007/s11135-009-9252-9
|View full text |Cite
|
Sign up to set email alerts
|

Does spatial visualization ability improve after studying technical drawing?

Abstract: Spatial ability, Spatial visualization, Inductive reasoning, Technical drawing, Training, Rasch model,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 11 publications
(14 reference statements)
2
11
0
2
Order By: Relevance
“…In contrast, there was no significant increase of the students' spatial ability scores throughout the Anatomy course. Additionally, and in accordance with Sorby's previous findings, 1,2,32 this work provides more evidence that spatial ability can be trained and improved. While males initially start at a higher initial spatial ability as measured with the MCT and PSVT:R than females, spatial ability gain is possible by both sexes.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…In contrast, there was no significant increase of the students' spatial ability scores throughout the Anatomy course. Additionally, and in accordance with Sorby's previous findings, 1,2,32 this work provides more evidence that spatial ability can be trained and improved. While males initially start at a higher initial spatial ability as measured with the MCT and PSVT:R than females, spatial ability gain is possible by both sexes.…”
Section: Resultssupporting
confidence: 91%
“…In a study performed by Prieto and Velasco, it was desired to know if spatial ability could be improved through a course that focused on technical drawing. The study concluded that spatial ability does improve, and the improvement was similar in men and women 2 . A similar study done by Németh focused on the development of spatial ability throughout a course focused on descriptive geometry.…”
Section: Introduction and Literature Reviewmentioning
confidence: 90%
See 2 more Smart Citations
“…En este sentido, según estudios previos (Baenninger & Newcombe, 1989;Sorby & Baartmans, 2000;Crown, 2001;Leopold et al, 2001;Prieto & Velasco, 2002;Alias et al, 2002;Rafi et al, 2005;Rafi et al, 2006;Prieto & Velasco, 2010), la visualización espacial se puede mejorar mediante entrenamiento y, por ello, los docentes están desarrollando continuamente metodologías que favorezcan las habilidades espaciales de los estudiantes, siendo mejor aceptadas por parte del alumnado las que se basan en las nuevas tecnologías de la información y del conocimiento (TIC) y crean una independencia del profesorado (Carrasco et al, 2008;Martín et al, 2009;Velasco, 2010). De hecho, aunque en algunos casos existen datos del poco uso de las TIC en la docencia universitaria (Gromaz et al, 2007), se puede afirmar que, de manera general, casi todas las ramas del conocimiento intentan modificar sus metodologías tradicionales tendiendo a usar las TIC en la docencia (Barragán et al, 2009;Mancho et al, 2009;Cárdenas & Paz, 2011).…”
Section: Introductionunclassified